Study on the Frequency Response Function of Viscoelastic Pipelines Using a Multi-Element Kevin-Voigt Model. (2015) - Gong, Jinzhe; Zecchin, Aaron; Lambert, Martin; Simpson, Angus
Abstract: This research focuses on the study of the frequency response function (FRF) of viscoelastic pipelines. The transfer matrix of a uniform viscoelastic pipeline is derived using the generalized multi-element Kevin-Voigt (K-V) model. The analytical expressions of the characteristic impedance and propagation operator are presented. The frequency response diagrams (FRDs) of a viscoelastic pipeline, with or without unsteady friction, are obtained numerically and compared with the FRDs of an elastic pipeline, with or without unsteady friction. It is verified that the pipe wall viscoelasticity introduces not only frequency-dependent shifting of the resonant frequencies but also frequency-dependent damping of the resonant peaks.